Optimisme Anak Jalanan Dalam Menghadapi Masa Depan - Alfianita, Nurhidayah; , Dr. Moordiningsih, M.Si, Psi (2016)
Optimism is a person's ability to look at the positive in everything. The increasing number of street children in East Java in 2016 was 4,528 which adds to concern the nation will be the future of street children. This study aims to understand and describe the optimism for the future which is owned by the street children. This research was conducted at red lights Ngawi. The research subjects or informants in this study amounted to 10 informants were busking at red lights in Ngawi. Sampling was done by purposive sampling technique. This study used a qualitative descriptive phenomenology approach, data collection using semi-structured interviews and observation descriptive. Guide interview was made based on the research questions and aspects of optimism that provision (permanence), it is easy to spread (pervasiveness) and the related with personal (personalization). The observations were made by means of direct observation of the behavior of the intensity of the informant. Data analysis techniques used in this research is interactive techniques consisting of four steps that must be done, the first stage is the stage of data collection, the second stage is the stage reduks data, the third stage is the stage of data display, and the fourth stage is the stage of conclusion and or verification stage. The study found that street children have optimism in the face of the future. Street children are able to recount in detail the problems faced during become street children, believe that bad events that happen only temporary. Forms of street children indicated optimism in the face of the future shown by always try and work hard without giving up. Factors that may inhibit the street children in the face of the future comes from internal factors within the child streets and external factors, namely the economic and environmental factors of street children.